WMD arms control in the Middle East prospects, obstacles and options - Muller, Harald; Muller, Daniel (The Ashgate Plus series in international relations and politics, 2015)
This volume, written under the auspices of the EU Consortium for Non-Proliferation and Disarmament determines the current state of diplomatic efforts to establish a weapons of mass destruction (WMD) free zone in the Middle East. In doing so, it provides insights into central actors' conflicting political positions, thereby explaining the stalemate of efforts to negotiate a WMD-free zone.